Connect the dots : the inspiring stories of 20 entrepreneurs without an MBA who dared to find their own path - Bansal, Rashmi (Ahmedabad Bushfire publishers, 2019)
Connect the dots is the story of 20 enterprising individuals without an MBA, who started their own ventures. They were driven by the desire to prove themselves.
Keywords: Success in business